2022
DOI: 10.1002/slct.202200174
|View full text |Cite
|
Sign up to set email alerts
|

Negligible Substituent Effect as Key to Synthetic Versatility: a Computational‐Experimental Study of Vinyl Ethers Addition to Nitrile Oxides

Abstract: A tangible substituent effect may be perceived as a good feature in developing an organic reaction. This work demonstrates that, on the contrary, a zero-slope Hammet plot should be sought. The synthesis of isoxazoles by consecutive cycloaddition of nitrile oxides to vinyl ethers and alcohols elimination was studied computationally and experimentally. We performed a Hammett study in silico to demonstrate a negligible substituent effect (i. e., broad substrate scope) in the addition of benzyl vinyl ether to nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 76 publications
(145 reference statements)
0
1
0
Order By: Relevance
“…In addition, using thermodynamic equations, there is a possibility to quantitatively estimate the ratio of regioisomers formed [38,42], what cannot be achieved with MEDT. The successful application of thermodynamic approach for study of cycloaddition of NOs to alkenes has been demonstrated in a number of recent works [34][35][36][37][38]43].…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%
“…In addition, using thermodynamic equations, there is a possibility to quantitatively estimate the ratio of regioisomers formed [38,42], what cannot be achieved with MEDT. The successful application of thermodynamic approach for study of cycloaddition of NOs to alkenes has been demonstrated in a number of recent works [34][35][36][37][38]43].…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%